ORGANIZATIONAL AND ECONOMIC FOUNDATIONS OF ENSURING UKRAINE’S ENERGY SECURITY - DYKHA, Valerii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates that to ensure Ukraine’s energy security, it is advisable to implement integrated management in organizational, economic and functional dimensions. The author describes the key elements, tools and expected results of the organizational, economic and functional context in the energy security management system. The organizational context of energy security management includes the formation of an institutional management structure; coordination between energy market entities; development of energy decentralization and local energy systems through relevant institutions, interaction models, platforms, which will lead to increased manageability and coordination; development of local energy sustainability of communities; integration of enterprises into common energy systems; reduction of dependence on centralized systems. Within the framework of the economic component of energy security management, the formation of investment and tariff mechanisms; economic logic of decentralization and modernization; stimulating the development of alternative energy; financial sustainability of the energy sector through the implementation of tariff policy; application of investment instruments; models of financing local energy in communities and industrial parks; stimulation of industrial energy efficiency; economic instruments of circular energy, which will lead to an increase in the investment attractiveness of the industry; modernization of infrastructure and an increase in the share of renewable energy; strengthening the energy autonomy of communities and energy hubs; accessibility of energy for business and the population. The functional component of energy security management is revealed by the importance of implementing management, forecasting, monitoring and assessment processes; feasibility studies of decisions; risk management through engineering management; monitoring and early warning systems of threats; risk management mechanisms; scenario analysis and a system of adaptive solutions that will ensure timely detection of threats; reduction of technical, cyber and economic risks; justification of management decisions; increased adaptability of the energy system to stresses. The author emphasizes the importance of synergy of these blocks in the system of ensuring energy security.